PEMAHAMAN HADITS TARBAWI BURHAN AL ISLAM AL ZARNUJI DALAM KITAB TA’LIM AL MUTA’ALLIM - Afwadzi, Benny; Fattah, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
This paper explores the understanding of tarbawi (education) hadith from one of the major influential clerics in the Islamic educational system, especially in pesantren. He is Burhan al Islam al Zarnuji with his landmark book Ta’lim al Muta’allim. The conclusion that can be drawn is that al Zarnuji has shades of sufistical view in understanding tarbawi hadith. This can be seen in his understanding of hadith on obligation to seek knowledge (thalab al ilmi faridhatun ‘ala kulli muslimin wa muslimatin), which is interpreted as ilm al hal, the science concerning the condition of the human religious or simplistically said as the religious sciences; and the hadith of intention of studying (innama al a’malu bi al niyyat) with the intention for the sake of the hereafter and religion, not mundane. Such an understanding is not something taken for granted, but it can be reinterpreted and perfected in accordance with the spirit of the times of context.